An exploration of the strategic collaboration between earthmoving machinery OEMs, licensed dealers and independent local resellers in a dynamic market - Rowley, Colin (University of Pretoria, 2025)
Mini Dissertation (MPhil (International Business))--University of Pretoria, 2024.